Effects of thermal treatments on the characterisation of microencapsulated chlorophyll extract of Caulerpa racemosa - Dewi, E. N.; Purnamayati, L.; Jaswir, Irwandi (Faculty of Food Science & Technology, UPM, 2022)
Caulerpa racemosa is a macroalga that has a green pigment, that is, chlorophyll. Chlorophyll is highly sensitive to damage during heat processing. In the present work, C. racemosa chlorophyll extract was microencapsulated with fish gelatine and Arabic gum coatings, using a freeze-drying technique, to protect against heat damage. The microcapsules were subjected to high temperatures (120, 140, and 160°C) for 5 h. The protective effect of microcapsules on chlorophyll stability was assessed by measuring chlorophyll a and b degradation, total phenolic content, antioxidant activity, functional group analysis, colour, particle size, and morphology via scanning electron microscopy. Chlorophyll b significantly decreased by 87.78% in comparison with chlorophyll a (61.49%) during heating; the characteristic green colour of chlorophyll changed to brownish-green following heat exposure. However, chlorophyll was still present in the microcapsules as detected by the presence of the functional group C=O bond at 1600 nm wavelength. The heat treatment did not affect microcapsule particle size and morphology. Particle size distribution ranged from 91.58 to 112.51 µm, and the microcapsule was flakeshaped. The activation energy of chlorophyll a was 19336.96 kJ/mol·K; this was higher than that of chlorophyll b, which was 1780.53 kJ/mol·K. Based on the results, microcapsules produced using fish gelatine and Arabic gum as coating materials were able to protect chlorophyll in C. racemosa extract from heat damage.